The perceptions of elite professional rugby league players and staff on the national rugby league annual calendar: A mixed-methods study - Fazackerley, L. A.; Minett, G. M.; Clark, J. D.; Kelly, V. G. (Sports Medicine - Open, 2023)
Background In recent years, the length of elite sporting competitions has raised concerns regarding player well-being, highlighting a need to review current match calendars. Therefore, this study aimed to explore the perceptions of elite National Rugby League (NRL) players and staff on the annual training and competition calendar from a player workload and well-being perspective.